KARAKTERISTIK PASIEN DENGAN UROLITHIASIS DI RSUD DR.DORIS SYLVANUS PALANGKARAYA KALIMANTAN TENGAH PERIODE 2022-2023 - Rinjani, Lalu Andika Surya; ambeng, Yudi; Nugrahini, Sinta; Patricia, Tisha; Nurfianto, Sigit (Fakultas Kedokteran Universitas Palangka Raya, 2025)
Urolithiasis is a common medical condition characterized by the formation of stones in the urinary tract, including the kidneys, ureters, bladder, and urethra. This disease can be caused by intrinsic factors such as age and genetics, as well as extrinsic factors including diet, dehydration, and environmental conditions. In Indonesia, urolithiasis cases are frequently encountered; however, comprehensive prevalence data remain limited, particularly at RSUD dr. Doris Sylvanus, Palangka Raya. This study aimed to identify the characteristics of patients with urolithiasis at RSUD dr. Doris Sylvanus during the 2022–2023 period, including age, gender, signs and symptoms, chief complaints, stone location, and applied management strategies. This was a retrospective descriptive study analyzing medical records of urolithiasis patients treated at RSUD dr. Doris Sylvanus from January 2022 to December 2023. The findings indicated that urolithiasis most commonly occurred in men aged 46–64 years. Prominent risk factors included gender and age. Most patients presented with flank pain as the main complaint, while the majority showed urinary retention as a clinical sign. Percutaneous nephrolithotomy (PCNL) was the most frequently applied treatment. Urolithiasis at RSUD dr. Doris Sylvanus predominantly affected elderly and middle-aged men, with flank pain as the chief complaint. This study provided essential insights for developing more effective treatment strategies for this condition